Assessing collegiate football team's willingness to monitor and track their physical readiness a study on the athlete's perceptions and behaviors - Cordova III, Rei Sergio A. 2000-
Physical readiness plays an integral part in developing a healthy and competitive athlete. This can be achieved by tracking and monitoring the athletes to avoid injury and enabling team managers to understand why some athletes do better, eliminating uncertainties and speeding up events. This study aimed to address a research gap by ascertaining the degree to which college football teams are inclined to monitor and maintain their physical readiness. Moreover, this research aimed to determine the athlete's perceptions and behavior on the impact of physical readiness on their performance. This study utilized a descriptive-qualitative design and used purposive sampling in determining the participants which are the members of a football team in a state university. There were eight participants who voluntarily consented to join the one-on-one structured interview through Zoom Meeting using an open-ended question to gather the relevant data necessary for the study. The data was analyzed using thematic analysis. After data analysis, it was found out that athletes are highly receptive in tracking and monitoring their physical readiness and that it helped the athletes become more motivated to perform better and felt that their coaching staff cared for their well-being. Additionally, three themes emerged: Receptiveness to Performance Tracking, Positive Impact on Athlete Performance and Team Dynamics and Drivers to the Team’s Overall Efficiency